Rhabdopeptides as Insect‐Specific Virulence Factors from Entomopathogenic Bacteria. Issue 15 (3rd September 2013) - Reimer, Daniela; Cowles, Kimberly N.; Proschak, Anna; Nollmann, Friederike I.; Dowling, Andrea J.; Kaiser, Marcel; Constant, Richard ffrench‐; Goodrich‐Blair, Heidi; Bode, Helge B.
Abstract Six novel linear peptides, named "rhabdopeptides", have been identified in the entomopathogenic bacterium Xenorhabdus nematophila after the discovery of the corresponding rdp gene cluster by using a promoter trap strategy for the detection of insect‐inducible genes. The structures of these rhabdopeptides were deduced from labeling experiments combined with detailed MS analysis. Detailed analysis of an rdp mutant revealed that these compounds participate in virulence towards insects and are produced upon bacterial infection of a suitable insect host. Furthermore, two additional rhabdopeptide derivatives produced by Xenorhabdus cabanillasii were isolated, these showed activity against insect hemocytes thereby confirming the virulence of this novel class of compounds.